2018
DOI: 10.1111/ijcp.13055
|View full text |Cite
|
Sign up to set email alerts
|

Real-world clinical outcomes and predictors of glycaemic and weight response to exenatide once weekly in patients with type 2 diabetes: The CIBELES project

Abstract: In a real-world setting, ExQW significantly decreased A1C, weight, blood pressure and lipids at 6 months. Our study identified higher baseline A1C as the sole independent predictor of glycaemic response to ExQW and higher BMI and previous DDP4i treatment as predictive factors of meaningful weight response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 24 publications
4
22
2
Order By: Relevance
“…Average weight reduction in LEAD, DURATION and AWARD programmes was 2.4 kg. This observation is confirmed by other RW studies with weight reductions ranging from 3.4 to 4.5 kg …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Average weight reduction in LEAD, DURATION and AWARD programmes was 2.4 kg. This observation is confirmed by other RW studies with weight reductions ranging from 3.4 to 4.5 kg …”
Section: Discussionsupporting
confidence: 89%
“…This observation makes sense from a pharmacokinetic point of view, based upon their lower plasma half‐life as compared to other drugs of the class and is in line with observations derived from phase III trials . At final follow‐up visit, a sustained reduction of HbA1c of 0.93% was achieved, along with a reduction of FPG of 24 mg/dL, both in keeping with reductions observed in many other RW studies with different GLP‐1 RA molecules . Nevertheless, when these results are compared to those of RCTs, differences are noticeable.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Outcomes at Week 26 were included as potential predictors in this analysis because the definition of response was linked to achievement of the HbA1c goal (<7.0% [<53 mmol/mol]) at Week 26, the end of the core treatment period. In previous studies, baseline characteristics such as HbA1c were found to be strong predictors of response in some instances, although not consistently . In the current model, response at Week 26 was a stronger predictor than any baseline characteristics tested.…”
Section: Discussioncontrasting
confidence: 60%